Intraspecific Variation on Palm Leaf Traits of Co-occurring Species—Does Local Hydrology Play a Role? - Emilio, Thaise; Pereira, Havle; Costa, Flávia R. C. (Frontiers in Forests and Global Change, 2021)
The study of plant species and trait distributions can provide answers to many of the ecological challenges of our times, from climate change to the biodiversity crisis. Although traits are classically measured at the species level, understanding intraspecific variation is necessary to determine the type of response species will have to climate change. Here we measured and analyzed seven leaf traits (leaf area - LA, specific leaf area - SLA, leaf thickness - LT, leaf dry mass content - LDMC, venation density - VD, stomata length SL and density - SD) across 14 locally dominant palm species (10 individuals/species) distributed along hydro-topographic gradients (1.4 to 37 m of terrain height above nearest drainage) of a central Amazonian forest to disentangle the role of species identity, relatedness and local hydrology on trait variation and covariation. Our results show that trait variation is not always larger between species than within species as expected. Intraspecific variation accounted for 23-74% of trait variation depending on the trait. Most of the variation happened at species level for SL, LA, LT and SD but not for SLA, VD and LDMC. For a third of the traits (LDMC, SLA, SD) we found some evidence of phylogenetic inertia. This lack of independency among traits is confirmed by the maintenance of a strong correlation among some of those traits after controlling for local environmental conditions. Intraspecific variation, however, was not related to height above nearest drainage for any of the traits. Most of trait-environment relationships were species-specific. Therefore, the change in palm trait composition detected along topography, from higher community means of SLA and LA, lower LT, LDMC, SL and SD in the wet valleys to opposite traits in drier plateaus, is mostly due to the turnover in species composition and relative abundance variation. We conclude that species have well-defined hydrological niches, but their large intra-specific variation in leaf traits does not contribute to the adjustment of individuals to the local hydrological conditions in this Amazonian Forest.